Perancangan Direksi Keet dan Hunian Sementara dengan Pendekatan Teritori Untuk Memperhatikan Privasi Pengguna - Eva Mei Wulandari; Asri Dinapradipta; Ima Defiana (Universitas Sebelas Maret Surakarta, 2024)
The creation of territories on site offices and temporary housing can affect the activities within them. This study explores the criteria for territories in site offices and temporary housing through user comfort and privacy. Qualitative research methods were used, with data collection through primary and secondary sources. Primary data was collected from field studies on projects in East Java, while secondary data was obtained from literature studies. The results of this study are design criteria that can be used as a reference for designing site offices and temporary housing with a territory concept, focusing on spatial comfort and privacy. The study shows that design criteria for spatial comfort are dimensions appropriate to body size to create optimal movement space in limited areas, whereas design criteria for privacy involve specific functions and clear circulation without disturbing users’ privacy.